Microstructural and tribological properties of induction cladded NiCrBSi/WC composite coatings - Kilicay, Koray; Buytoz, Soner; Ulutan, Mustafa (Elsevier Science Sa, 2020)
In this study, the Ni-based WC reinforced MMC coating was conducted by a novel process called induction cladding (IC). Powder mixtures of NiCrBSi and NiCrBSi-WC were pre-located on an AISI 316 stainless steel chamber and heated at 1200 degrees C for 20 min with a high frequency induction coil in an Ar atmosphere and cooled in the same environment. The coating layer showed an intense and non-porous metallurgical bond to the stainless steel. As a result of the microstructural and phase analysis of the coating layer, gamma-nickel main phases with Ni3B, Ni3Fe, Ni3Si, Cr23C6, CrB and Cr7C3 were determined in dendritic and cellular regions. In addition, WC and W2C phases were observed in reinforced samples. The average hardness value of the IC clad coating was 2.8 times higher, compared to AISI 316, due to the formation of hard carbide and boride phases in the interdendritic regions. The COF values and wear rate of the cladded samples were decreased compared to the AISI 316. Increasing the amount of WC reinforced powder used in the IC process increased the wear resistance by up to 10 times to be compared with the stainless steel AISI 316.
Keywords: NiCrBSi-WC; Induction cladding; Microstructure; Friction and wear